2016
DOI: 10.1186/s13102-016-0036-y
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of post-exercise muscle oxygenation and duration of cycling exercise

Abstract: BackgroundAerobic adaptations following interval training are supposed to be mediated by increased local blood supply. However, knowledge is scarce on the detailed relationship between exercise duration and local post-exercise blood supply and oxygen availability. This study aimed to examine the effect of five different exercise durations, ranging from 30 to 240 s, on post-exercise muscle oxygenation and relative changes in hemoglobin concentration.MethodsHealthy male subjects (N = 18) performed an experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 47 publications
(77 reference statements)
2
7
0
Order By: Relevance
“…These adaptive microcirculation responses after stretching are similar to the responses observed after arterial occlusion (10) and exercise (15,28,34). It has been speculated that poststretching hyperemia may contribute to the loss of myogenic tone and accumulation of vasodilator metabolites (15,28,34). This study also showed a similar reaction with a rapid increase in DtHb and DTOI after stretching.…”
Section: Discussionsupporting
confidence: 81%
“…These adaptive microcirculation responses after stretching are similar to the responses observed after arterial occlusion (10) and exercise (15,28,34). It has been speculated that poststretching hyperemia may contribute to the loss of myogenic tone and accumulation of vasodilator metabolites (15,28,34). This study also showed a similar reaction with a rapid increase in DtHb and DTOI after stretching.…”
Section: Discussionsupporting
confidence: 81%
“…We have shown in previous studies that isolated 30 s work intervals might lead to lower cardiovascular responses compared to 3 min work intervals [23]. However, repeated 30 s work-interval bouts could nevertheless be effective in a similar way compared to longer interval durations.…”
Section: Discussionmentioning
confidence: 72%
“…In general, a better microvascular O 2 distribution is indicated by a lower ∆HHb/∆VO 2 ratio. This method was used previously in relation to microvascular O 2 adjustment during exercise on-transient [8,22] as well as a description of microvascular O 2 availability during and after exercise [11,23,24].…”
Section: Methodsmentioning
confidence: 99%
“…In one study, 18 subjects performed 5 exercise bouts (30, 60, 90, 120, and 240 s) at 80% of peak oxygen uptake separated by 5 min recovery periods. Post-exercise oxygen availability and local blood supply increased significantly until the 90 s bout and plateaued thereafter [28]. Exercise intensities of ≥80% VO 2 peak induce the highest post-exercise oxygen availability locally.…”
Section: Parameters During Exercisementioning
confidence: 93%